TATA KELOLA SAMPAH UNTUK MEWUJUDKAN KOTA BERSIH DI KECAMATAN PEMANGKAT - Herfrien Nurufitriza E.42008002 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
The title of the study is "Strategic Public Works Department of Human Settlements In Handle Waste In District Pemangkat". This study aimed to find out How to waste management operations in the District Pemangkat and waste management techniques in District Pemangkat. The title of the study is taken based on the existing problems, such as piles of garbage that is not transported, the proposition prasaranan inadequate waste transport and the number of officers who are not proportional to the volume of waste in the District Pemangkat. For waste management can be 3R principle, the reduction (reduce) the volume of waste, use (reuse) and sorting trash (recycle), so that the garbage problem can be resolved. This research is qualitative research and data collection using observation techniques, interview techniques and techniques Dokumntasi, while using techniques of data analysis techniques summarize data (data reduction), explained (data display) and concluded (verification). Based on this research, that the operations of waste management in the district is still not optimal Pemangkat dikarenakaan some barriers, such as inadequate prasaranan proposition and are destroyed, the number of officers that do not comply with current waste volume that the accumulation of rubbish and not transported, plus more not the way to manage waste. That is done only pembakaranan to reduce the volume of waste, while for the use and selection is not done because they limited facilities and lack of personnel PUCK. To that end, the need for additional waste management facilities and infrastructure so that the waste can be used and reused, and the addition PUCK officers to address growing waste volumes.Keywords: Waste Management and Waste Management Techniques (reduce, reuse and recycle).Herfrien Nurufitriza, Tata Kelola Sampah Untuk Mewujudkan Kota Bersih